Teratogenic effects of the neonicotinoid thiacloprid on chick embryos (Gallus gallus domesticus). (August 2018) - Salvaggio, Antonio; Antoci, Francesco; Messina, Antonino; Ferrante, Margherita; Copat, Chiara; Ruberto, Claudia; Scalisi, Elena Maria; Pecoraro, Roberta; Brundo, Maria Violetta
Abstract: Thiacloprid is an insecticide belonging to the family of neonicotinoids, substances initially underestimated for their potential adverse effects, that they may manifest in the long term leading to an extensive use. The objective of this study was to evaluate the effect at increasing concentrations of thiacloprid on chick embryos development. The research was carried out on 75 fertile eggs of Gallus gallus domesticus . The eggs were opened after 10, 15 and 20 days of incubation and in treated embryos were observed developmental alterations, growth retardation, limbs defects and ectopia viscerale. The histological analysis showed hepatic steatosis and haemorrhages both in the liver and in the lungs. Moreover, the immunohistochemical analysis performed on the liver sections showed a strong positivity only for the erythrocytes to the anti-CYP1A antibody. Thiacloprid exposure increases the risks of teratogenic effects especially at the higher doses tested, therefore its use should be more controlled and limited. Since the literature on the topic is lacking, then the human health impacts resulting from neonicotinoids exposure is not yet fully understood, and, our data will be helpful to allow the assessment of an oral reference dose and health risk characterization. Graphical abstract: Highlights: Neonicotinoids are synthetic insecticides formulated for crop protection. Thiacloprid is a first generation neonicotinoid. Evaluation the potential teratogenic effects of thiacloprid in embryonated eggs of chicken. Teratogenic effects was highlighted above all in the terminal period of development. The erythrocytes showed a strong positivity to the anti-CYP1A antibody.